Causes and effects of urban water scarcity on households in Daye town administration, Southern Ethiopia - Melese Tefo Worasa; Asfaw Gnefato; Mulugeta Bakkalo; Yirga Goraw (Cogent Social Sciences, 2024)
This descriptive research was conducted in Daye town, Ethiopia, to assess the causes and effects of urban water scarcity on households. To this end, stratified sampling from probability, purposive and convenience from non-probability sampling techniques as well as primary and secondary sources of data were used. A questionnaire was distributed among selected 279 households and analyzed using SPSS-version-21. The major indicator of water scarcity used is the Falkenmark indicator. The study found that the sample households had an amount of water consumption per individual that was 10.52-liter per day. Water is considered to be accessible if an individual consumes 1700 m3 per year, according to the Falkenmark indicator. However, the individual in the town receives 3.83 m3 per year, which is an absolute scarcity. The causes of water scarcity were population growth and urbanization, lack of finance, and lack of institutional, technological, and managerial capacity. The effects were health and economic. There was waterborne disease due to a shortage of water and quality problems of available water sources found from unprotected nearby rivers. The economic cost included money spent on the purchase of water from vendors and the repair of old pipes. Likewise, the study revealed that service provision regarding water was poor and unequal. Thus, the study recommends that the drilling of additional boreholes, capacity building of water service offices, sustainable financing strategy, and participation of NGOs and private sectors in the water system are compulsory.